Pengaruh Model Pembelajaran Reciprocal Learning Terhadap Kemampuan Menulis Puisi Pada Siswa - Yanti Claudia Sinaga; Rosmawaty Harahap (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
The purpose of this study was to find out how the sharing learning model has an impact on the ability to write poetry in class VIII students of SMP Negeri 8 Medan in the 2022/2023 academic year. This research involved all students in class VIII SMP Negeri 1 Delitua, a total of 303 students in 10 classes. Of the 303 students, 29 were selected to be the research sample. This study uses a one-group pre-test post-test experimental design. The method used is a description test. Test "t" data is used to test the hypothesis. The results show that the students' ability to write poetry before using the Reciprocal Learning learning model is classified as poor, with an average value (mean) of 60.51, while their ability after using this model is quite good, with an average value (mean) of 81.37 . Furthermore, the results of the hypothesis testing show that the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted, because tcount is greater than ttable, which is 8.01 greater than 2.045. This shows that the ability of class VIII students of SMP Negeri 8 Medan to write poetry texts is influenced by the sharing learning model.